Current Perspectives on Immunotherapy in the Peri-Operative Setting of Muscle-Infiltrating Bladder Cancer - Zucali, Paolo Andrea; Cordua, Nadia; D'Antonio, Federica; Borea, Federica; Perrino, Matteo; De Vincenzo, Fabio; Santoro, Armando (Frontiers in Oncology, 2020)
Patients with muscle-infiltrating bladder cancer (MIBC) present a high risk of postoperative recurrence and death from metastatic urothelial cancer despite surgical resection. Before the use of peri-operative chemotherapy, about half (52%) of patients undergoing radical cystectomy had had a relapse of tumor disease within 5 years of surgery. However, when peri-operative cisplatin-based chemotherapy is added to radical cystectomy for patients with MIBC it provides limited benefit in terms of survival, disease recurrence and development of metastases, at the expense of toxic effects. In fact, a significant proportion of patients still recurs and die to metastatic disease. Given the success of immune-oncological drugs in metastatic urothelial cancer, several trials started to test them in patients with non-metastatic MIBC either in neo-adjuvant and adjuvant setting. The preliminary results of these studies in neo-adjuvant setting are showing great promise, confirming the potential benefits of immunotherapy also in patients with non-metastatic MIBC. The aim of this review is to present an overview of developments happening on the introduction of immunotherapy in peri-operative setting in non-metastatic urothelial cancer. Moreover, an analysis of the critical issues regarding how best customize the delivery of immunotherapy to optimize efficacy and minimize the adverse effects, with particular focus on potential prognostic and predictive molecular biomarkers, is done.